2002
DOI: 10.1086/339521
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T Cell Responses to a Variant Antigen of the Malaria ParasitePlasmodium falciparum,Erythrocyte Membrane Protein–1, in Individuals Living in Malaria‐Endemic Areas

Abstract: Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP-1) is a variant antigen on the surface of malaria-infected red blood cells. Antibody responses to PfEMP-1 correlate with immunity, and, therefore, PfEMP-1 may be a good candidate for a malaria vaccine. However, the specificity of CD4 T cells required for a protective variant-specific antibody response is not known. We have measured the CD4 T cell response to 3 different regions that are relatively homologous among different PfEMP-1 variants. The respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
3
15
2
Order By: Relevance
“…Seventeen and 16 of 33 donors were positive for IFN-␥ and IL-10 production, respectively. As described previously (20), there was generally an inverse or no association between IL-10 production and CD4 T cell proliferation. Interestingly, some individuals responded by IFN-␥ production and no cell division, and we observed an unexpected positive association between IFN-␥ and IL-10 concentrations (Spearman's coefficient ϭ 0.62, p ϭ 0001, data not shown).…”
Section: Assessment Of Cd4 T Cell Division and Cytokine Production Insupporting
confidence: 71%
See 3 more Smart Citations
“…Seventeen and 16 of 33 donors were positive for IFN-␥ and IL-10 production, respectively. As described previously (20), there was generally an inverse or no association between IL-10 production and CD4 T cell proliferation. Interestingly, some individuals responded by IFN-␥ production and no cell division, and we observed an unexpected positive association between IFN-␥ and IL-10 concentrations (Spearman's coefficient ϭ 0.62, p ϭ 0001, data not shown).…”
Section: Assessment Of Cd4 T Cell Division and Cytokine Production Insupporting
confidence: 71%
“…Two recombinant protein fragments of PfEMP-1 were expressed and purified as described elsewhere (20). CIDR1-␣ was obtained from a PfEMP-1 gene of the Malayan Camp laboratory isolate of P. falciparum (GenBank accession no.…”
Section: Preparation and Purification Of Pfemp-1 Fragmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The knowledge of B-and T-cell activity directed to specific epitopes of PfEMP1 in naturally exposed humans is very limited (1), and no studies have reported PfEMP1-specific immune responses in the cord blood from neonates born to mothers with malaria. Epidemiological studies suggest that pregnancy-associated malaria increases the likelihood of early infection in the newborn (6,18), possibly as a result of antigen exposure inducing immunosuppressive pathways during fetal development (2,3).…”
mentioning
confidence: 99%